Comparison of canal transportation and centering ability of K-files the ProGlider file and G-file : a micro-computed tomography study of curved canals - Van der Vyver, Petrus Jacobus (University of Pretoria, 2016)
Dissertation (MSc)--University of Pretoria, 2015.